Aligning conservation and development goals with rural community priorities: capacity building for forest health monitoring in an extractive reserve in Brazil - Sabina C. Ribeiro (Resilience Alliance, 2020)
Rural communities are important stewards of forests that provide valuable ecological services. This makes them vital allies to outside organizations seeking to support conservation and development initiatives. However, rural communities also have priorities and needs that may not align with the goals of conservation and development projects. This makes effective engagement of communities by outside organizations an important challenge. When rural communities lose traditional livelihood options, they prioritize economic benefits as a condition for participating in projects, and they exhibit "project fatigue" when many projects are imposed on their time. We reflect on our experience in seeking to align the goals of a conservation and development project with community priorities in the Chico Mendes Extractive Reserve in Acre, Brazil. Our project featured capacity building for monitoring forest health to foster participation in payments for ecosystem services programs. Although we pursued prior consultations and designed participatory activities, and although we combined knowledge transmission with skills training, participation declined. That prompted our team to consult with community members, which generated important insights about expectations of immediate economic remuneration, community political cultures, communicative practices, and differences among local constituencies. These insights motivated adaptation of our practices via several strategies, such as focusing on young adults and holding workshops as part of community assemblies, which aligned project goals with the priorities of community members to improve project outcomes.